Experimental investigation on wear behaviour of laser sintered and unsintered Inconel 718 in vibratory finishing. (2022) - Karthik, R.; Elangovan, K.; Girisha, K.G.; Shankar, S.
Abstract: Vibratory finishing is a mass finishing process employed in the industries to deburr, clean and fabricate an isotropic finishing on metallic materials. In this process the manual involvement is self-effacing. In the present investigation the tribological behaviour of the laser sintered and Unsintered Inconel 718 components due to comparative motion between the samples and media have been investigated. The ceramic media is the extensively favourite media type. Scanning electron microscope and EDAX spectrum analysis was used to analyse the surface morphology and chemical composition of the components respectively. The wear rate was measured on the basis of weight loss of the components with respect to media. The effect of media and test duration on the wear behaviour was analysed and reported. The surface micro hardness and surface roughness of the samples was investigated. The investigated results indicated that due superior surface hardness and density in the sintering, the sintered samples shows extreme wear resistance as compared to unsintered samples.